Nitrous oxide emission from agricultural soils: Application of animal manure or biochar? A global meta-analysis. (1st May 2021) - Shakoor, Awais; Shahzad, Sher Muhammad; Chatterjee, Nilovna; Arif, Muhammad Saleem; Farooq, Taimoor Hassan; Altaf, Muhammad Mohsin; Tufail, Muhammad Aammar; Dar, Afzal Ahmed; Mehmood, Tariq
Abstract: Organic amendments (animal manure and biochar) to agricultural soils may enhance soil organic carbon (SOC) contents, improve soil fertility and crop productivity but also contribute to global warming through nitrous oxide (N2 O) emission. However, the effects of organic amendments on N2 O emissions from agricultural soils seem variable among numerous research studies and remains uncertain. Here, eighty-five publications (peer-reviewed) were selected to perform a meta-analysis study. The results of this meta-analysis study show that the application of animal manure enhanced N2 O emissions by 17.7%, whereas, biochar amendment significantly mitigated N2 O emissions by 19.7%. Moreover, coarse textured soils increased [ l n R R ‾  = 182.6%, 95% confidence interval (CI) = 151.4%, 217.7%] N2 O emission after animal manure, in contrast, N2 O emission mitigated by 7.0% from coarse textured soils after biochar amendment. In addition, this study found that 121–320 kg N ha − 1 and ⩽ 30 T ha −1 application rates of animal manure and biochar mitigated N2 O emissions by 72.3% and 22.5%, respectively. Soil pH also played a vital role in regulating the N2 O emissions after organic amendments. Furthermore, > 10 soil C: N ratios increased N2 O emissions by 121.4% and 27.6% after animal and biochar amendments, respectively. Overall, animal manure C: N ratios significantly enhanced N2 O emissions, while, biochar C: N ratio had not shown any effect on N2 O emissions. Overall, average N2 O emission factors (EFs) for animal manure and biochar amendments were 0.46% and −0.08%, respectively. Thus, the results of this meta-analysis study provide scientific evidence about how organic amendments such as animal manure and biochar regulating the N2 O emission from agricultural soils. Graphical abstract: Image 1 Highlights: Organic amendments (animal manure and biochar) may increase SOC stocks but also influence N2 O emissions. Animal manure significantly increased N2 O emission by 17.7%. Biochar amendment significantly mitigated N2 O emissions by 19.7%. Maximum reduction was observed with medium doses of animal manure (121–320 kg N ha-1) and biochar (⩽ 30 T ha −1 ).